QUALITY OF LIFE IN PATIENTS WITH DIABETIC NEPHROPATHY - de los Ríos Castillo, José Lauro; Sánchez Sosa, Juan José; Barrios Santiago, Pedro; Ávila Rojas, Teresa Luzeldy (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Chronic renal insufficiency (CRI) due to diabetic nephropathy (DN), represents in Mexico a matter of concern in public health. This illness has an impact so much physical as emotional along the process of the chronicity, this process deteriorates the quality of people’s life that suffer it. For such reason, the purpose of the present investigation is to determine the impact of the deterioration of the quality of life in a sample of patients with diabetic nephropathy. It was carried out an expo-facto, of traverse type study, in this study we try to identify and typify their possible functional peculiarities. The fellows that participated in the study were 100 patients that attend to the continuos peritoneal dialysis program, in a hospital of the IMSS, of the capital of San Luis’ State Potosí, diagnosed by their own doctors with DN. The deterioration of the quality of life was measured with the scale of quality of life related with the health (QOLRH), in its validated version and standardized to spanish. The dependent variable to consider was the evaluation of the index of deterioration of the quality of life estimated through the QOLRH scale. The independent variable understood the evolution time of the chronic-degenerative condition of the DN of the selected patients, as well as some socio-demographic aspects. The results revealed that 100% of the studied sample deals with some grade of deterioration in its quality of life in the valued areas that included the scale. The areas of interaction stand out with the team of health, the sexual dysfunction, the emotional and physical aspects, among others. Having more risk in the deterioration, those patients with more than ten years of evolution of the suffering with DM-2, the educational level, over 50 years age. We conclude that the grade of deterioration of the quality of life in this type of patient with DN is progressive and associated to the degenerative evolution of the illness.